Plasma Exchange and Glucocorticoids in Severe ANCA-Associated Vasculitis - Walsh, Michael; Merkel, Peter A; Peh, Chen-Au; Szpirt, Wladimir M; Puéchal, Xavier; Fujimoto, Shouichi; Hawley, Carmel M; Khalidi, Nader; Floßmann, Oliver; Wald, Ron; Girard, Louis P; Levin, Adeera; et al. (The New England journal of medicine, 2020)
BACKGROUND: More effective and safer treatments are needed for antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis. METHODS: We conducted a randomized trial with a 2-by-2 factorial design to evaluate the use of plasma exchange and two regimens of oral glucocorticoids in patients with severe ANCA-associated vasculitis (defined by an estimated glomerular filtration rate of <50 ml per minute per 1.73 m2 of body-surface area or diffuse pulmonary hemorrhage). Patients were randomly assigned to undergo plasma exchange (seven plasma exchanges within 14 days after randomization) or no plasma exchange (control group). Patients were also randomly assigned to follow either a standard-dose regimen or a reduced-dose regimen of oral glucocorticoids. Patients were followed for up to 7 years for the primary composite outcome of death from any cause or end-stage kidney disease (ESKD). RESULTS: Death from any cause or ESKD occurred in 100 of 352 patients (28.4%) in the plasma-exchange group and in 109 of 352 patients (31.0%) in the control group (hazard ratio, 0.86; 95% confidence interval [CI], 0.65 to 1.13; P = 0.27). The results were similar in subgroup analyses and in analyses of secondary outcomes. We also assessed the noninferiority of a reduced-dose regimen of glucocorticoids to a standard-dose regimen, using a noninferiority margin of 11 percentage points. Death from any cause or ESKD occurred in 92 of 330 patients (27.9%) in the reduced-dose group and in 83 of 325 patients (25.5%) in the standard-dose group (absolute risk difference, 2.3 percentage points; 90% CI, -3.4 to 8.0), which met the criterion for noninferiority. Serious infections at 1 year were less common in the reduced-dose group than in the standard-dose group (incidence rate ratio, 0.69; 95% CI, 0.52 to 0.93), but other secondary outcomes were similar in the two groups. CONCLUSIONS: Among patients with severe ANCA-associated vasculitis, the use of plasma exchange did not reduce the incidence of death or ESKD. A reduced-dose regimen of glucocorticoids was noninferior to a standard-dose regimen with respect to death or ESKD. (Funded by the U.K. National Institute for Health Research and others; PEXIVAS Current Controlled Trials number, ISRCTN07757494; ClinicalTrials.gov number, NCT00987389.).
Keywords: Kidney Failure, Chronic; kombinovaná terapie; ANCA-asociované vaskulitidy; Humans; indukční chemoterapie; nemoci ledvin; lidé středního věku; Glucocorticoids; Dose-Response Relationship, Drug; Female; Aged; dospělí; Induction Chemotherapy; senioři; lidé; Administration, Oral; výměna plazmy; imunosupresiva; Adult; Immunosuppressive Agents; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; ženské pohlaví; chronické selhání ledvin; Male; rituximab; Middle Aged; incidence; glukokortikoidy; Incidence; Cyclophosphamide; Rituximab; vztah mezi dávkou a účinkem léčiva; aplikace orální; Combined Modality Therapy; mužské pohlaví; Plasma Exchange; cyklofosfamid; Kidney Diseases